1999
DOI: 10.1093/humrep/14.2.560
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8 potentiates the effect of interleukin-1-induced uterine contractions

Abstract: The aim of this research was to study the effect of exogenous interleukin (IL)-8, IL-1 and IL-8 + IL-1 on uterine contractions in rabbits. Four equal groups of non-pregnant rabbits (n = 24) were investigated using either placebo or experimental drugs in the form of vaginal suppositories. The suppositories contained human recombinant IL-8 (200 ng), IL-1 (200 ng), IL-8 (200 ng) + IL-1 (200 ng) or vehicle Witepsol base, 500 microliters). Subsequently, the plasma concentration of prostaglandin (PG) E2 was estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 22 publications
1
14
0
1
Order By: Relevance
“…The mechanism involved in the up-regulation of PGHS-2 activity with the onset of labour is uncertain, but several stimuli including IL-1b are known to increase PGHS-2 expression via the transcription factor nuclear factor k B (NFkB) (Allport et al 2001). Indeed, most data suggest that inflammatory cytokines increase myometrial contractility via increased PG synthesis (Khatun et al 1999). The multiple regression data revealed associations between the levels of PGHS-2 mRNA and those of IL-8, IL-6 and IL-1b and our in vitro studies confirmed the important role played by IL-1b; in contrast both IL-6 and IL-8 had a small effect.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism involved in the up-regulation of PGHS-2 activity with the onset of labour is uncertain, but several stimuli including IL-1b are known to increase PGHS-2 expression via the transcription factor nuclear factor k B (NFkB) (Allport et al 2001). Indeed, most data suggest that inflammatory cytokines increase myometrial contractility via increased PG synthesis (Khatun et al 1999). The multiple regression data revealed associations between the levels of PGHS-2 mRNA and those of IL-8, IL-6 and IL-1b and our in vitro studies confirmed the important role played by IL-1b; in contrast both IL-6 and IL-8 had a small effect.…”
Section: Discussionmentioning
confidence: 99%
“…For example, IL-1b enhances contraction of airway, uterine and gastrointestinal smooth muscles. (19)(20)(21) Andre et al (22) reported IFN caused contraction of primary cultures of rat vascular smooth muscle cells that was blocked by verapamil. Cytokine potentiation of bronchoconstrictors such as acetylcholine, histamine and leukotrienes is also probably an important component of airway hyper-reactivity seen in asthma.…”
Section: Production Of Cytokines and Chemokines By Smooth Musclesmentioning
confidence: 99%
“…The degrees of inflammatory infiltrate and cytokine expression correlate (4), and it has been suggested that the invading leukocytes are the major source of the proinflammatory cytokines (6). The proinflammatory cytokines in turn increase leukocyte infiltration and promote both the expression of contraction-associated peptides and uterine contractions (7,8). Furthermore, and more importantly in some circumstances, the proinflammatory cytokines may contribute to fetal morbidity and mortality (9).…”
mentioning
confidence: 99%
“…Its production is increased in myometrium, cervix, decidua, and fetal membranes with labor (4, 10), and its levels are increased in amniotic fluid in the presence of chorioamnionitis and with the duration of labor (11,12). It acts synergistically with IL-8 to increase prostaglandin production and uterine contractions in the rabbit (7), and in vitro in human myometrial cells, it increases prostaglandin H synthase 2 (PGHS-2) expression via p38 MAPK activation and increased nuclear factor B (NFB) DNA binding in myometrium and amnion (13)(14)(15). IL-1␤ also increases IL-8 expression in fetal membranes and lower segment fibroblasts (8) and reduces prostaglandin dehydrogenase activity in the intact fetal membrane disc model (16).…”
mentioning
confidence: 99%